Helium release during shale deformation: Experimental validation. (16th July 2016) - Bauer, Stephen J.; Gardner, W. Payton; Heath, Jason E.
Abstract: This work describes initial experimental results of helium tracer release monitoring during deformation of shale. Naturally occurring radiogenic 4 He is present in high concentration in most shales. During rock deformation, accumulated helium could be released as fractures are created and new transport pathways are created. We present the results of an experimental study in which confined reservoir shale samples, cored parallel and perpendicular to bedding, which were initially saturated with helium to simulate reservoir conditions, are subjected to triaxial compressive deformation. During the deformation experiment, differential stress, axial, and radial strains are systematically tracked. Release of helium is dynamically measured using a helium mass spectrometer leak detector. Helium released during deformation is observable at the laboratory scale and the release is tightly coupled to the shale deformation. These first measurements of dynamic helium release from rocks undergoing deformation show that helium provides information on the evolution of microstructure as a function of changes in stress and strain. Key Points: Helium release is measured real time during shale deformation using a mass spectrometer Helium release rate is empirically related real time to volume strain Release of naturally occurring helium in the subsurface may be used to monitor changes in stress, strain, and permeability in shale formations